Phytoplankton flora of Tanguar haor ecosystem in Bangladesh: Cyanophyta, Pyrrhophyta, Chrysophyta and Euglenophyta (Journal of Biodiversity Conservation and Bioresource Management, 2019)
The present paper is dealt with the composition and density of the population of pelagic phytoplankton collected from two studied stations, namely Watch Tower and Rauar Station of Tanguar Haor in Sunamganj District. Plankton belonging to the divisions Cyanophyta, Pyrrhophyta, Chrysophyta and Euglenophyta were studied from bimonthly collected samples during 2017 and 2018. Division Cyanophyta was represented by the occurrence of 17 species followed by Chrysophyta (16 spp.), Euglenophyta (4 spp.) and Phyrrhophyta (2 spp.). The most dominant plankton taxon was Dinobryon sertularia Ehrenberg whose density was 374 ×103 ind/l and 137.5 ×103 ind/l at Watch Tower and Rauar Station, respectively. Euglenoid population was relatively poorer compared to the other groups of phytoplankton. Abundant population of D. sertularia designates the Tanguar Haor ecosystem as moderate in terms of productivity. A total of 39 species recorded from three algal divisions, namely Cyanophyta, Pyrrhophyta, Chrysophyta and Euglenophyta. Tanguar Haor ecosystem was included with mean phytoplankton population of Cyanophyta, Pyrrhophyta, Chrysophyta and Euglenophyta.J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(1): 105-112